Perancangan Display Visual Kuantitatif Pada Sistem Manusia Mesin - Mujahidin, M (Department Industrial Engineering, University of Muhammadiyah Malang, 2000)
Work system consist of man and machine system, human senses need a tool to respons all kind of stimulus such an information given by machine or outside of system, so that human cancontrol machine well. It means that we need display design based on the characteristic of human sense asbility in catching informationThere are many kind of display that can be made depend with information characteristicsThis research will give quantitative visual display design fixed to information characteristic givenand also consider with human visual ability accepting an information from outside